Development of methods for forming the cost of production and assessment of its impact on the efficiency of an industrial enterprise - Pererva, Petro; Kobielieva, Tetiana; Keršys, Robertas; Nagy, Szabolcs; Kosenko, Oleksandra; Tkachova, Nadiia; Marchuk, Lesia; Kosenko, Andriy; Tkachov, Maksym; Pohorielov, Serhii (Technology audit and production reserves, 2025)
The paper considers the influence of the level of production cost on the overall efficiency of the functioning of industrial enterprises in the conditions of the modern economy and its economic potential. The value of the cost of production as one of the key factors determining the efficiency of an industrial enterprise and the level of its economic potential is considered. The main components of the cost, methods of its accounting and optimization opportunities are analyzed. Practical recommendations for improving production efficiency through cost management are given. A comprehensive analysis of the structure and dynamics of production costs has been carried out, the main factors influencing the formation of the cost of production, in particular, resource intensity, energy consumption, organizational and technological level of production and managerial approaches have been identified. In this research, let’s focus on the importance of cost rationalization and increasing the level of accounting and control over costs as key tools for ensuring the competitiveness of the enterprise. To control the cost, such methods as break-even analysis, accounting by centers of responsibility, regulatory accounting, calculation by types of products are proposed for use. The effective use of these methods allows to identify inefficient costs, conduct a comparative analysis of costs by periods, and make informed management decisions. Among the main ways to reduce the cost of production, was identified: introduction of energy-saving technologies, automation of production processes, improvement of logistics, inventory management, revision of supply contracts, as well as motivation of employees to increase labor productivity. On the example of a generalized profile of an industrial enterprise, the influence of various components of costs on the profitability of products is analyzed. It has been found that timely changes in the market situation and avoid unprofitable decisions.